MENGENALI KECANDUAN SITUS PORNO PADA REMAJA: GAMBARAN MENGENAI FAKTOR PENYEBAB DAN BENTUK KECANDUAN SITUS PORNO REMAJA - Wahid Hasyim; Azhariah Nur B. Arafah; Sitti Shaqylla; Umniyah Saleh (Universitas Negeri Makassar, 2018)
Adolescence is a phase where people want to experience new things in their life that this phase is vulnerable for their development. Various vulnerabilities can effect adolescence, which one of them is addicted and accessing to porn sites. This research used a mixed method approach between qualitative and quantitative research using descriptive form that aims to obtain an overview of the causes and forms of addiction to porn sites that experienced by adolescence. Informants in this research were 112 adolescence who consisted of 59 men and 53 women who were located in the city of Makassar aged 15-18 years old and never access porn sites, where researches used purposive sampling. This research used a addicted to porn sites scale that was adapted by the author based on Porn Addiction Assessment of Young as well as a questionnaire prepared by the researcher using a literature review regarding addiction porn sites as a research instrument. The data obtained will be analyzed using qualitative analysis model with a content analysis form and then processed using statistical methods of frequency distribution. The results in this research shows that pornographic in adolescent males is higher than adolescent girls. Factors that causes a person becomes addicted to porn sites are divided into external and internal, which external factors in this case is from friends, is the biggest factor that causes porn sites addiction in adolescents. However, internal factors, such as their own desires and curiosity will also affect adolescents addicted to porn sites. In addition, most teenagers in Makassar are classified as a compulsive sexual user. The researchers also found a new characteristic of user, namely defensive user based on the informants responses.